The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1530/jme-15-0264
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 promotes proliferation and differentiation of MC3T3-E1 osteoblasts by MAPKs activation

Abstract: Glucagon-like peptide-1 (GLP1) and its receptor agonist have been previously reported to play a positive role in bone metabolism in aged ovariectomized rats and insulinresistant models. However, whether GLP1 has a direct effect on the proliferation and differentiation of osteoblasts or any cellular mechanism for this potential role is unknown. We examined the effects of the GLP1 receptor agonist exendin-4 on the proliferation, differentiation, and mineralization of mouse osteoblastic MC3T3-E1 cells. GLP1 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 38 publications
0
36
1
Order By: Relevance
“…It has been proposed that GLP-1 could promote c-Fos transcription in osteoblasts in combination with ATP, facilitating the participation of GLP-1 in bone turnover (47). It has been shown that exendin-4 enhanced the proliferation and differentiation of osteoblasts partly mediated by MAPK pathways, including ERK1/2, p38, and JNK pathways (48). It was also proposed that liraglutide regulated MC3T3-E1 cells differentiation mediated by adenosine monophosphate-activated protein kinase/mammalian target of rapamycin signaling (49).…”
Section: The Potential Mechanisms Of the Glp-1 Effects On Bone Metabomentioning
confidence: 99%
“…It has been proposed that GLP-1 could promote c-Fos transcription in osteoblasts in combination with ATP, facilitating the participation of GLP-1 in bone turnover (47). It has been shown that exendin-4 enhanced the proliferation and differentiation of osteoblasts partly mediated by MAPK pathways, including ERK1/2, p38, and JNK pathways (48). It was also proposed that liraglutide regulated MC3T3-E1 cells differentiation mediated by adenosine monophosphate-activated protein kinase/mammalian target of rapamycin signaling (49).…”
Section: The Potential Mechanisms Of the Glp-1 Effects On Bone Metabomentioning
confidence: 99%
“…Wnt5a, a noncanonical Wnt ligand, activates signalling through both β-catenin-independent mediators, such as c-Jun N-terminal Kinase (JNK) and the β-catenin-dependent pathway [17]. Feng et al found that activated JNK signalling promotes the osteogenic differentiation of mouse MC3T3-E1 cells [18]. Furthermore, previous studies have demonstrated that mechanical stress also enhanced the expression of Wnt5a/Wnt5b mRNA in stem cells and autonomously promoted osteogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Rac1 and Rac2 have critical roles in osteoclasts and skeletal metabolism . Rac1 can be significantly stimulated by exendin‐4 to promote differentiation and mineralization of mouse osteoblastic MC3T3‐E1 cells . Rac was also shown to negatively regulate TGF‐β‐stimulated vascular endothelial growth factor synthesis via inhibition of p38 MAPK in osteoblasts .…”
Section: Discussionmentioning
confidence: 99%